Transfusion complications in thalassemia patients: a report from the Centers for Disease Control and Prevention (CME). Issue 4 (25th July 2013) - Vichinsky, Elliott; Neumayr, Lynne; Trimble, Sean; Giardina, Patricia J.; Cohen, Alan R.; Coates, Thomas; Boudreaux, Jeanne; Neufeld, Ellis J.; Kenney, Kristy; Grant, Althea; Thompson, Alexis A.
<x xml:space="preserve">Abstract</x> Background Transfusions are the primary therapy for thalassemia but have significant cumulative risks. In 2004, the Centers for Disease Control and Prevention (CDC) established a national blood safety monitoring program for thalassemia. This report summarizes the population and their previous nonimmune and immune transfusion complications. Study Design and Methods The CDC Thalassemia Blood Safety Network is a consortium of centers longitudinally following patients. Enrollment occurred from 2004 through 2012. Demographics, transfusion history, infectious exposures, and transfusion and nontransfusion complications were summarized. Logistic regression analyses of factors associated with allo‐ and autoimmunization were employed. Results The race/ethnicity of these 407 thalassemia patients was predominantly Asian or Caucasian. The mean ± SD age was 22.3 ± 13.2 years and patients had received a mean ± SD total number of 149 ± 103.4 units of red blood cells (RBCs). Multiorgan dysfunction was common despite chelation. Twenty‐four percent of transfused patients had previous exposure to possible transfusion‐associated pathogens including one case of babesia. As 27% were immigrants, the infection source cannot be unequivocally linked to transfusion. Transfusion reactions occurred in 48%, including allergic, febrile, and hemolytic; 19% were alloimmunized. Common antigens were E, Kell, and C. Years of transfusion was the strongest predictor of alloimmunization. Autoantibodies occurred in 6.5% and were associated with alloimmunization (p < 0.0001). Local institutional policies, not patient characteristics, were major determinants of blood preparation and transfusion practices. Conclusion Hemosiderosis, transfusion reactions, and infections continue to be major problems in thalassemia. New pathogens were noted. National guidelines for RBC phenotyping and preparation are needed to decrease transfusion‐related morbidity.